Business model innovation for sustainability: a new framework - Rosaria Ferlito; Rosario Faraci (Innovation & Management Review, 2022)
Purpose - Sustainable business model innovation (SBMI) is a change in the way a firm operates in order to create positive impacts or to reduce negative consequences for the environment and the society. The aim of this paper is to explain what pathways a firm can take when it implements a sustainable business innovation process in line with Sustainable Development Goals (SDGs). Design/methodology/approach - The article starts with the analysis of the existing literature about BMI and SBMI in order to extrapolate the main elements of these topics. Findings - Thanks to the combined information from academic and nonacademic sources, the study proposes a new framework. It is divided into three sectors: value proposition, value capture delivery and value capture according to the main studies about the business model. Research limitations/implications - Regarding theoretical implications, this study contributes to developing a theory of both BMI and sustainable innovation. Indeed it helps in the understanding of the dynamic vision about how the business model changes in order to incorporate triple sustainability. Practical implications - From a practical view, the paper can serve as a guideline for corporate reorganization. Originality/value - The new framework differs from some recent academic efforts first of all for its theoretical characteristics: BMI construct and not business model concept is the core of the framework. The business model represents the subject of innovation, not its vehicle. Another unique aspect that can be derived from the approach adopted is that it links theoretical with practical sources.
Keywords: 650; Innovation; Sustainable business model innovation; Sustainability; SDG; Business modeling; Framework